Analisis Rasio Keuangan: Return on Assets Ratio (ROA), Return On Equity Ratio (ROE) dan Net Interest Margin (NIM) Pada Bank Mestika Periode 2019-2023 - Devi, Haura Awalin Nurista (Maliki Interdisciplinary Journal, 2025)
This study analyzes the financial performance of Bank Mestika during the 2019-2023 period using three key indicators: Return on Assets (ROA), Return on Equity (ROE), and Net Interest Margin (NIM). The analysis shows that Bank Mestika’s ROA improved from 2019 to 2021 but declined in 2022-2023, remaining above Bank Indonesia’s healthy threshold. ROE also exhibited a positive trend until 2021 but decreased in the last two years, indicating challenges in maintaining profitability. NIM remained relatively stable above 5%, reflecting the efficiency of productive asset management despite some fluctuations. This study recommends strategies to enhance operational efficiency, diversify financing products, manage non-performing financing risks, and adopt financial technology to improve the bank’s competitiveness. These findings are expected to provide a foundation for Bank Mestika’s management to strengthen its competitive position in the Islamic banking industry.